2011
DOI: 10.1128/aem.00533-11
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Emerging Biogeography of the Neutrophilic Iron-Oxidizing Zetaproteobacteria

Abstract: Members of the neutrophilic iron-oxidizing candidate class Zetaproteobacteria have predominantly been found at sites of microbially mediated iron oxidation in marine environments around the Pacific Ocean. Eighty-four full-length (>1,400-bp) and 48 partial-length Zetaproteobacteria small-subunit (SSU) rRNA gene sequences from five novel clone libraries, one novel Zetaproteobacteria isolate, and the GenBank database were analyzed to assess the biodiversity of this burgeoning class of the Proteobacteria and to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
158
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(167 citation statements)
references
References 63 publications
8
158
0
1
Order By: Relevance
“…M34, which was isolated as a microaerophilic Fe(II) oxidizer from a microbial mat at a deep-sea hydrothermal vent at Loihi Seamount (Hawaii) by McAllister et al (76). Our study thus shows that microaerophilic Fe(II)-oxidizing Zetaproteobacteria are also naturally present in coastal marine sediments.…”
Section: Coexistence Of Different Physiological Types Of Fe(ii) Oxidimentioning
confidence: 67%
See 2 more Smart Citations
“…M34, which was isolated as a microaerophilic Fe(II) oxidizer from a microbial mat at a deep-sea hydrothermal vent at Loihi Seamount (Hawaii) by McAllister et al (76). Our study thus shows that microaerophilic Fe(II)-oxidizing Zetaproteobacteria are also naturally present in coastal marine sediments.…”
Section: Coexistence Of Different Physiological Types Of Fe(ii) Oxidimentioning
confidence: 67%
“…In contrast to the nitrate-reducing and phototrophic Fe(II) oxidizers, marine microaerophilic Fe(II) oxidizers belong to the Zetaproteobacteria, as the ones that we found in the two different sediments from Aarhus Bay appear to be metabolically very restricted. All currently known isolates originate from ironrich environments and are obligate microaerophilic Fe(II) oxidizers (37,38,40,76). Although it was found that they carry the genes for nitrate reduction (75,103), there is so far no evidence from growth experiments that they can actually live by that type of metabolism.…”
Section: Coexistence Of Different Physiological Types Of Fe(ii) Oxidimentioning
confidence: 99%
See 1 more Smart Citation
“…An operational taxonomic unit (OTU) was defined as a group of sequences with 97% sequence similarity to each other. These sequences were compared with reference sequences from McAllister et al (2011) to determine which global OTU these sequences correlated with.…”
Section: Sequence Classification and Otu Designationmentioning
confidence: 99%
“…To date, the Zetaproteobacteria have only been identified in habitats with high ferrous iron concentrations. Within this context, they have been detected in a wide range of environments from hydrothermal vent sites, such as Loihi Seamount, where they can dominate the microbial community (Rassa et al, 2009;Emerson and Moyer, 2010;McAllister et al, 2011;Fleming et al, 2013), to coastal environments, where they may be involved in biocorrosion of steel structures such as ships and pilings (Dang et al, 2011;McBeth et al, 2011).…”
Section: Introductionmentioning
confidence: 99%